Study and analysis of different adverse effects associated with psychotropic drugs in psychiatry outpatient unit of a teaching hospital (International Journal of Research in Pharmacology & Pharmacotherapeutics, 2021)
Adverse drug Reactions (ADRs) are one of the important causes for morbidity and mortality [1, 2]. Pharmacovigilance, the art of identification, assessing and prevention of ADRs is gaining its importance as these unintended responses may attribute to noncompliance or at times discontinuation of the therapy. The main aim of Pharmacovigilance is identification and hence prevention of potential harm caused by a drug to the patient. It starts from early stages of the clinical trials and continues through the entire life cycle of drug including premarketing and post marketing phases [3]. In psychiatry the first and major choice of management is pharmacotherapy and may often require combination of drugs to attain required therapeutic effect. [4] Usage of medications for short term in most of the cases increase the chance of relapse of symptoms, hence most of the guidelines  indicate a long term usage which could be a contributing reason for developing ADRs. [5-7] In addition stringent rules in carrying out clinical trials for psychiatric medications and elimination of co-morbidities and other clinically important conditions makes usage and monitoring of psychiatric medications a great challenge clinically. [8] The adverse reactions profile with psychiatric medications are often disabling, effecting quality of life, creating social stigma, at times fatal like Neuroleptic malignant syndrome or serious skin reactions or sometimes irreversible as in tardive dyskinesia. [9, 10] As mental disorders are valued judgments with valid scientific or objective evidence, assessment and evaluation may vary. [11, 12] A close monitoring allows early identification, when followed by rectification where ever possible may prevent a potential harm or permanent disability. In countries like India where psychiatric disorders are effecting populations of all age groups at an alarming pace there is a need for monitoring of ADRs as these may lead to misconception among patients regarding treatment for psychiatric disorders